2010
DOI: 10.1246/cl.2010.932
|View full text |Cite
|
Sign up to set email alerts
|

Subpicosecond UV-pump and IR-probe Spectroscopy of 9-Fluorenone in Deuterated Acetonitrile and Methanol

Abstract: The vibrational dynamics of the CO stretching mode of 9-fluorenone (FL) in CD3CN and CD3OD were studied by sub-picosecond UV-pump and IR-probe spectroscopy. We found that the CO stretching band is blue-shifted by hydrogen-bond formation in the S1 state but red-shifted in the S0 state. In both CD3CN and CD3OD, the time evolution of the transient absorption spectrum was observed on a picosecond time scale, likely because of vibrational cooling and hydrogen-bond dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…15 Tominaga and co-workers reinvestigated the hydrogen bond dynamics in the excited state of FL in CD 3 OD using subpicosecond-resolved visible pump−IR probe spectroscopy to show hydrogen bond-breaking and -reorganization processes. 27,28 Han et al, however, advocated hydrogen bond strengthening upon electronic excitation of these chemical systems from the results of time-dependent density functional theory calculations. 19,20 FL has a single hydrogen bond-accepting site (CO group) and forms 1:1 and/or 1:2 hydrogen-bonding complexes with hydrogen bond-donating solvents through association with either and both of the available lone pairs of electrons on the oxygen atom of the carbonyl group, respectively (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…15 Tominaga and co-workers reinvestigated the hydrogen bond dynamics in the excited state of FL in CD 3 OD using subpicosecond-resolved visible pump−IR probe spectroscopy to show hydrogen bond-breaking and -reorganization processes. 27,28 Han et al, however, advocated hydrogen bond strengthening upon electronic excitation of these chemical systems from the results of time-dependent density functional theory calculations. 19,20 FL has a single hydrogen bond-accepting site (CO group) and forms 1:1 and/or 1:2 hydrogen-bonding complexes with hydrogen bond-donating solvents through association with either and both of the available lone pairs of electrons on the oxygen atom of the carbonyl group, respectively (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen bonds inuence various properties of the solute, such as its electronic states and the relaxation processes. 9-Fluorenone (FL) has a carbonyl group which can form hydrogen bonds, and spectroscopic studies [9][10][11][12][13][14] as well as theoretical calculations 15 have been reported on the nature of the excited state of FL. The vibrational dynamics of FL in alcohol solutions have been reported in the electronic ground state 12 and the excited state.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrational dynamics of FL in alcohol solutions have been reported in the electronic ground state 12 and the excited state. 10,13,14 Using sub-picosecond UV-pump infrared (IR)-probe spectroscopy we have observed transient IR absorption spectra of FL in acetotrnile-d 3 and methanol-d 4 . 13 By comparison with theoretical calculations of the vibrational structure in the S 1 state, 15 we assigned the vibrational bands observed in the transient spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrafast vibrational spectroscopy has been proven to be a powerful technique as it probes the vibrational frequency changes in real time and the vibrational frequencies are often exquisitely sensitive to the H-bond interaction. In recent years, time-resolved infrared (TRIR) spectroscopy has been explored in great detail, which has advanced the microscopic understanding of static and dynamic features of H-bonding in equilibrium and nonequilibrium conditions. Hydrogen bonding reorganization and fluctuation around a solute significantly influence charge transfer, electron transfer, and excited-state deactivation processes of the solute. Real-time measurements of H-bond formation and reorganization provide a detailed picture of the site-specific interaction between solute and solvent molecules and bring mechanistic insight into hydrogen-bond-induced chemical and photochemical reactivity.…”
Section: Introductionmentioning
confidence: 99%